Transcriptome Sequencing Analysis Provides Insights Into the Response to Fusarium oxysporum in Lilium pumilum. (March 2019) - He, Xiangfeng; Li, Wanyue; Zhang, Wenzhu; Jin, Xiaotong; Shenkute, Awraris Getachew; Aynalem, Tessema; Xu, Shufa; Wang, Wenhe
Lily basal rot, caused by Fusarium oxysporum f. sp. lilii, is one of the most serious diseases of lily. Although the lily germplasm which is resistant to F. oxysporum has been used in disease-resistant breeding, few studies on its molecular mechanism of disease resistance have been reported. To comprehensively study the mechanism of resistance to F. oxysporum, transcriptome sequencings of root tissues from Lilium pumilum inoculated with F. oxysporum or sterile water for 6, 12, or 24 h were performed. A total of 50 GB of data were obtained from the transcriptome sequencings of the 6 L. pumilum samples, and 217 098 Unigenes were obtained after the de novo assembly, of which 38.36% Unigenes were annotated. The sequencing results showed that the numbers of differentially expressed genes at 6, 12, and 24 h after inoculation compared with the control were 111, 254, and 2500, respectively. The functional enrichment analysis of the differentially expressed genes showed that several pathways were involved in responses of L. pumilum, mainly including starch and sucrose metabolism, glycolysis/gluconeogenesis, phenylpropanoid biosynthesis, plant hormone signal transduction, flavonoid biosynthesis, vitamin B6 (VB6) biosynthesis, acid biosynthesis, proteasome, and ribosome. Transcription factor analysis revealed that the WRKY and ERF families played important roles in responses of L. pumilum to F. oxysporum . The results of this study elucidate the molecular responses to F. oxysporum in lily and lay a theoretical foundation for improving lily breeding and strategies for lily basal rot resistance.